An Analysis Of Teachers’ Strategy In Teaching Reading Comprehension Of Senior High School At Kecamatan Dampelas - Endang Puspita Sari; Darmawan Darmawan; Wahyudin Wahyudin; Muhammad Arid (Hasanuddin University, 2026)
This study aimed to find the strategies used by English teachers in teaching reading comprehension at senior high schools and to identify the most frequently used strategies. This study employed a descriptive qualitative research design, collecting data through questionnaires and interviews with 4 English teachers. The results showed that teachers used various strategies in teaching reading comprehension, and scaffolding, QARs, monitoring comprehension, and memorizing were the most frequently used strategies. These strategies were highly effective in helping students understand reading texts and improving their reading abilities. This study also revealed that scaffolding and QARs strategies enabled teachers to provide appropriate assistance and support to students who did not understand reading texts, allowing students to better comprehend the texts. The findings of this study were expected to be used as a reference for English teachers in developing effective reading comprehension teaching strategies.